Comparative Evaluation of the Inhibitory Potential of Synthetic N-Heterocycles, Cu/Fe3O4@SiO2 Nanocomposites and Some Natural Products against Non-Resistant and Antibiotic-Resistant Acinetobacter baumannii - Jalal Mardaneh; Hamid Beyzaei; Seyed Hadi Hashemi; Behzad Ghasemi; Abbas Rahdar (Tabriz University of Medical Sciences, 2020)
Background: Acinetobacter baumannii is a common infectious agent in hospitals. New antimicrobial agents are identified and prepared to combat these bacterial pathogens. In this context, the blocking potentials of a series of synthesized N-heterocyclic compounds, Cu/Fe3O4@SiO2 nanocomposites, glycine, poly-L-lysine, nisin and hydroalcoholic extracts of Trachyspermum ammi, Curcuma longa and green tea catechins were evaluated against non-resistant and multidrug-resistant strains of A. baumannii.Methods: Solutions of heterocyclic derivatives and hydroalcoholic extracts of Trachyspermum ammi, Curcuma longa and green tea catechins were prepared at initial concentration of 10240 μg ml-1 in 10% DMSO. Other compounds were dissolved in water at the same concentrations. Their in vitro inhibitory activity was assessed by determination of IZD, MIC and MBC values.Results: Glycine, poly-L-lysine, nisin, Curcuma longa and green tea catechins extracts, and thiazoles 3a, 3d and 3f were ineffective at their initial concentrations. Heterocyclic derivatives 7a-f, 3c, 3e and 3h, Cu/Fe3O4@SiO2 nanocomposites and Trachyspermum ammi extract could block the growth of bacterial strains with IZDs (7.40-15.51 mm), MICs (32-1024 µg ml-1) and MBCs (128-2048 µg ml-1).Conclusion: Among synthetic chemicals and natural products, the best antimicrobial effects were recorded with (E)-2-(5-acetyl-4-methylthiazol-2-yl)-2-(thiazolidin-2-ylidene)acetonitrile (7b) and the extract of Trachyspermum ammi. It is imperative that their toxic and histopathologic effects were assessed in future researches. It is predicted that the essential oil of Trachyspermum ammi will improve its antibacterial activities.